The Effect of School Environment on Students' Learning Outcomes At SDN Legok II Tangerang - Shafaa Brilianti; Een Unaenah; Eka Yulyawan Kurniawan (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2026)
A supportive school environment significantly improves students' learning outcomes in Natural and Social Sciences (IPAS) at the elementary school level. This study aims to determine whether the school environment influences IPAS learning among fourth-grade students at SDN Legok II Tangerang. A quantitative ex post facto approach was employed to analyze the impact of the school environment on students' IPAS learning outcomes, involving 54 students from classes IV-A and IV-B. Data were collected using a questionnaire regarding the school environment and a test to measure students' IPAS learning outcomes. The results indicate that the school environment plays a role in enhancing the quality of students' IPAS learning. A relationship exists between the school environment and IPAS learning, with a correlation coefficient of 0.455, indicating that improvements in the school environment are associated with better student learning outcomes. The study reveals that the school environment accounts for 20.7% of the influence on students' IPAS learning, while the remaining 79.3% is attributable to factors outside the scope of this research. Thus, creating a supportive school environment can facilitate better IPAS learning and play a crucial role in student achievement in Natural and Social Sciences.